2012
DOI: 10.5420/jsltr.01.01.3318
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Effects of Personality Traits, Self-esteem, Language Class Risk-taking and Sociability on Chinese University EFL Learners' Performance in English

Abstract: Although the interactive effects of different variables in language learning have increasingly become the focus of recent research, the interaction of such variables as personality traits, self-esteem, language class risk-taking and sociability has not been much investigated.Hence, the present study explored the predicting effects of these variables on Chinese EFL learners' performance in English at the tertiary level. A 68-item survey involving 934 firstyear undergraduate non-English majors revealed that: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
7
0
3
Order By: Relevance
“…Contemporary research has demonstrated how the high level of cognitive structuration corresponded with the high level of communication skills and with the process of coping with stressful and demanding situations (Výrost, Ruisel, 2000, Bar-Tal andGuinote, 2002). Liu (2012) and Liu-Lu, Liu (2016) considered the factor of risk-taking in the process of learning a foreign language as one of the essential in the context of tolerance of ambiguity. They found out a significant influence of the factor of risk-taking on the performance of the university students in EFL.…”
Section: Tolerance Of Ambiguitymentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary research has demonstrated how the high level of cognitive structuration corresponded with the high level of communication skills and with the process of coping with stressful and demanding situations (Výrost, Ruisel, 2000, Bar-Tal andGuinote, 2002). Liu (2012) and Liu-Lu, Liu (2016) considered the factor of risk-taking in the process of learning a foreign language as one of the essential in the context of tolerance of ambiguity. They found out a significant influence of the factor of risk-taking on the performance of the university students in EFL.…”
Section: Tolerance Of Ambiguitymentioning
confidence: 99%
“…Thus, research in the field of tolerance of ambiguity (Liu, 2012;Clarke, 2012;Stranovská et al, 2013;Sarmány-Schuller, 2014;Liu-Lu, Liu, 2016;Švecová, Pavlovičová, 2016; and others) represents a wide field of investigation, induction as well as deduction. Presumably, tolerance of ambiguity is a skill necessary for all foreign language teaching programs; it enhances natural foreign language communication as well as in-service teachers` foreign language self-esteem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have pointed to the relationship between and the effects of a number of these psychological constructs and the level of S/FL oral proficiency. To put it more clearly, studies have been done on the effects of or the relationship between English oral proficiency and self-confidence (Gurler, 2015;Juhana, 2012), learners' attitudes toward English (Norton & Toohey, 2001;Zeinivand, Azizifar, & Gowhary, 2015), self-esteem (Ahour & Hassanzadeh, 2015;Devi & Qiqiehi, 2016;Koosha, Ketabi, & Kassaian, 2011), anxiety (Mai, 2011;Woodrow, 2006), motivation (Ihsan, 2016;Juhana, 2012), shyness (Al Nakhalah, 2016;Ostovar, Safaee, & Sobhanifar, 2015), fear of making mistakes (Sato, 2003), personality types, introversion /extroversion (Mai, 2011;Meihua, 2012), and self-efficacy (Khatib & Maarof, 2015;Liu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…reprezentuje nepretržitú tvorbu, jedinečný a neopakovateľný obraz ľudskej kognície. Z toho dôvodu výskum v oblasti kreativity v cudzojazyčnej výučbe z kognitívneho pohľadu (Liu, 2012;Clarke, 2012;Stranovská a kol., 2013;Bírová, 2013;J. Henriksen, Mishra, Fisser, 2016, Müglová, Malá, Stranovská 2017 predstavuje neobmedzené pole pôsobnosti, bádania, dedukcií a indukcií.…”
unclassified